The Miocene Petrified Forest of Lesvos, Greece: Research and Geoconservation Activities - Nickolas Zouros (Geoconservation Research)
The Petrified Forest of Lesvos is a Protected Natural Monument showing standing and lying petrified tree trunks, preserved by intense volcanic activity in the early Miocene. The Natural History Museum of Lesvos Petrified Forest contributed significantly to scientific research, conservation, exhibition, promotion and international recognition of the Lesvos Island UNESCO Global Geopark, a founding member of the European and the Global Geoparks Network. The Lesvos Geopark includes a variety of other volcanic, tectonic, geomorphological and coastal geosites. Lesvos Geopark works to identify, protect and promote geosites through the establishment of an interpretation infrastructure, a network of walking trails linking geosites and other sites of interest, relevant information points and eco-tourism infrastructure as well as the organization of exhibitions, scientific events and congresses as well as environmental education programs and activities.